2015
DOI: 10.1149/2.0851508jes
|View full text |Cite
|
Sign up to set email alerts
|

Study of Structural Colors of Anodic Alumina Thin Films Prepared by a Point Electrode

Abstract: For this study, porous anodic alumina thin films with annular structural colors were fabricated in a phosphoric acid electrolyte by the one-step oxidation of an aluminum (Al) sheet. In this case, small carbon balls were used as the cathode and an Al sheet used as the anode, with the distance between cathode and anode remaining adjustable. Electron microscopy shows that the different parts of films are different in microstructure. Results additionally reveal that the depth and aperture of nano-holes diminished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Yang et al studied the structural colors of anodic porous alumina films prepared using a carbon ball as a point cathode electrode for normal DC anodization and reported that the gradient of the film thickness was caused by the symmetrical distribution of current density on the aluminum anode. 21 Even in this study, although the current distribution could not be measured on the aluminum bipolar electrode, the blue coloration indicates that the film thickness was non-uniform; the current density might have non-uniformly varied outward from the center of the aluminum specimen. Because the movement of the electric charge periodically reverses direction between the positive and negative, ion transport under an AC electric field is much more complicated than in DC.…”
Section: Resultsmentioning
confidence: 70%
“…Yang et al studied the structural colors of anodic porous alumina films prepared using a carbon ball as a point cathode electrode for normal DC anodization and reported that the gradient of the film thickness was caused by the symmetrical distribution of current density on the aluminum anode. 21 Even in this study, although the current distribution could not be measured on the aluminum bipolar electrode, the blue coloration indicates that the film thickness was non-uniform; the current density might have non-uniformly varied outward from the center of the aluminum specimen. Because the movement of the electric charge periodically reverses direction between the positive and negative, ion transport under an AC electric field is much more complicated than in DC.…”
Section: Resultsmentioning
confidence: 70%
“…32 The use of cost-effective techniques to evaluate electrochromic processes results very attractive for quality controls reducing the price of devices without compromising their performance. [33][34][35] Digital image acquisition (DIA) as a non-contact and versatile technology used to characterize colored surfaces of electrochromic polymers, [36][37][38] fruits, 39 sensors, 40,41 solar cells, 42 metal surfaces 43,44 can be a feasible option especially when it is necessary to characterize the whole electrode surface. Despite this, the use of DIA to evaluate dynamic electrochemical processes is not widely extended.…”
mentioning
confidence: 99%